SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA RUMAH MAKAN "PAK DE" - Sanjaya Zulkarnain (2022)
"Technology developments at this time make it easier for users to carry out business activities selling food and beverages such as the current Pak De Restaurant, making owners have to look for strategies that can attract consumers' interest. The Pak De Restaurant in Central Jakarta is a restaurant that sells various types of food and beverages. The problem with ordering menus at Pak De's Restaurant in Central Jakarta is still using a manual system, namely ordering using paper and payment without a receipt so there is often a build-up of data, data errors, data damage, loss of payment receipts. The method used is the method of data collection and the method of developing the system that is made.